1995
DOI: 10.1002/mrd.1080400313
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stimulators of protein kinases A and C and modulators of phosphorylation on plasminogen activator activity in porcine oocyte‐cumulus cell complexes during in vitro maturation

Abstract: Effects of phorbol myristate acetate (PMA), dibutyryl cyclic AMP (dbcAMP), 6-dimethylaminopurine (6-DMAP), and okadaic acid (OA) on plasminogen activator (PA) activity in porcine oocyte-cumulus cell complexes (POCC) in vitro were determined. Cumulus cell-enclosed oocytes were collected from 1-4 mm antral follicles and cultured in TCM-199 with 0.3% polyvinylpyrrolidone for 48 hr. PA activities in POCC were quantified using SDS-PAGE, casein-agar zymography, and densitometry. Two plasminogen-dependent lytic zones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…In porcine oocytes, PKC was observed to participate in the regulation of the resumption of meiotic maturation (Jung et al, 1992;Coskun and Lin, 1995;Kim and Menino, 1995;Su et al, 1999;Shimada et al, 2001). Fan et al (2002b) demonstrated a change in the localization of PKC -α, -β I , -γ in maturing porcine oocytes and after their activation.…”
Section: Which Signalling Cascades Remained Silent In No-induced Oocymentioning
confidence: 99%
“…In porcine oocytes, PKC was observed to participate in the regulation of the resumption of meiotic maturation (Jung et al, 1992;Coskun and Lin, 1995;Kim and Menino, 1995;Su et al, 1999;Shimada et al, 2001). Fan et al (2002b) demonstrated a change in the localization of PKC -α, -β I , -γ in maturing porcine oocytes and after their activation.…”
Section: Which Signalling Cascades Remained Silent In No-induced Oocymentioning
confidence: 99%
“…Studies in starfish, Xenopus, and mammalian oocytes have reached an identical conclusion that maintenance of a high level of cAMP and active PKA play a critical role in mei-otic arrest (Maller and Krebs, 1977;Speaker and Butcher, 1977;Sadler and Maller, 1981;Eppig and Downs, 1984;Bornslaeger et al, 1986;Eppig, 1989;Smith, 1989;Tornell and Hillensjo, 1993;Kim and Menino, 1995;Rose-Hellekant and Bavister, 1996). Pharmacological manipulations to increase cAMP levels or injection of PKA in mammalian oocytes isolated from their follicles invariably produce a blockade of meiotic resumption, and phosphodiesterase inhibitors, such as the xanthine IBMX, also block spontaneous mammalian oocyte maturation (Conti et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Degradation of cAMP by a phosphodiesterase type IIIA (PDE3A) leads to a decrease of PKA activity and initiates resumption of meiosis in rodent oocytes (Conti 2002, Kovo et al 2006. Similarly, in porcine oocytes, resumption of meiosis is also associated with a decrease in cAMP concentration and subsequent inactivation of PKA (Kim & Menino 1995).…”
Section: Introductionmentioning
confidence: 99%